Improving the technical and operational characteristics of the railway carriage - Maryna Bulakh (Scientific Reports)
Abstract The article discusses methods to enhance the technical and operational characteristics of railway carriages through innovative design solutions. It primarily focuses on reducing the weight of the railway carriage by modifying the supporting floor, which improves energy efficiency and performance. Mathematical modeling and strength calculations have demonstrated that the modified supporting floor can significantly reduce maximum equivalent stresses, thereby ensuring the reliability and safety of the structure. Dynamic modeling has confirmed that the new design meets regulatory standards for stability and safety at various speeds. A comparative analysis with existing models of railway carriages shows that the new design can reduce weight by 1.4–5.4%, leading to substantial improvements in energy efficiency and lower operating costs. The results highlight the significance of optimizing railway carriage design to achieve enhanced strength, safety, and economic efficiency in railway transport.